THE REPRESENTATION OF SPUNK IN THE SHORT STORY ENTITLED SPUNK BY ZORA NEALE HURSTON - Asmarani, Ratna (Faculty of Humanities, Diponegoro University, 2019)
AbstractThe aim of this paper is to analyze the representation of spunk (courage) in Zora Neale Hurston’s short story entitled Spunk. The focus is on the three protagonists, two males and one female. The concepts of courage consisting of its meaning, types, and characteristics are used to support the contextual literary analysis. The result shows that each protagonist has unique type of courage whether the courage hiding the cowardice, the courage emerging after conquering fear even though having to face deadly risk, or the courage to decide done by the female considered as the dependent second sex.Keywords: spunk, courage, contextual literary analysis Abstrak Tujuan dari makalah ini adalah untuk menganalisis representasi keberanian dalam cerita pendek Zora Neale Hurston yang berjudul Spunk. Fokus kajian pada tiga protagonis, dua laki-laki dan satu perempuan. Konsep keberanian yang terdiri atas makna, jenis, dan karakteristiknya digunakan untuk mendukung analisis sastra kontekstual. Hasilnya menunjukkan bahwa masing-masing protagonis memiliki jenis keberanian yang unik apakah keberanian yang menyembunyikan kepengecutan, keberanian yang muncul setelah menaklukkan ketakutan meskipun harus menghadapi risiko yang mematikan, atau keberanian untuk memutuskan yang dilakukan oleh perempuan yang dianggap sebagai jenis kelamin kedua yang bergantung pada laki-laki.Kata kunci: kejagoanan, keberanian, analisis sastra kontekstual